Kepemimpinan Kepala Madrasah dalam Pengembangan Profesionalisme Guru di Bidang Teknologi Informasi - Arief, Muhammad (KURIOSITAS: Media Komunikasi Sosial Keagamaan, 2018)
This article describes the headmaster of the madrasah leadershipand his strategies and roles in developing teacher professionalism, and to describe the headmaster's leadership model in developing teacher professionalism in MAN 2 Parepare. The type of research was qualitative research with a case study design by taking data sources to the head of the madrasa and teachers through data collection techniques of observation, interviews, and documentation. The results of the study indicate that the headmaster's leadership must be able to carry out the task as an educator, manager, administrator, motivator, supervisor, innovator and leader. This study implications was the need for leadership attention to subordinates through the development of teacher professionalism. It is expected that each leader will immediately reevaluate his leadership model so far, and always strive to improve the professional development of teachers in the madrasa he leads.